Role of Molecular Agents and Targeted Therapy in Clinical Trials for Women With Ovarian Cancer. Issue 4 (1st April 2011) - Ledermann, Jonathan A.; Marth, Christian; Carey, Mark S.; Birrer, Michael; Bowtell, David D.L.; Kaye, Stan; McNeish, Iain; Oza, Amit; Scambia, Giovanni; Rustin, Gordon; Stehman, Frederick B.; Gershenson, David; et al.
Abstract : There is now a greater understanding of the molecular pathways in ovarian cancer, and using this knowledge, a large number of new therapeutic agents can be tested. The success of these drugs will depend on selecting drugs that target known key dysfunctional molecular pathways. To make best use of these compounds, prognostic and predictive biomarkers need to be identified. Novel methods of assessment such as functional imaging need to be developed as additional biological end points to evaluate these therapies. Promising antitumor activity has been observed with some drugs, and careful consideration is needed to determine in what circumstances new agents, such as antiangiogenic compounds, could be considered as a standard therapy. These areas were discussed at the 4th Ovarian Cancer Consensus Conference.